2021
DOI: 10.1016/j.buildenv.2020.107467
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Three Ventilation Strategies in a prefabricated COVID-19 inpatient ward

Abstract: Prefabricated inpatient wards have been proven to be an efficient alternative to quickly extend the caring capacity for patients. In this study, three typical ventilation strategies were studied using computational fluid dynamics in a prefabricated Coronavirus disease 2019 double-patient ward. Pollutants are the respiratory droplets and aerosols injected from two manikins. They are modelled as particles with different diameters (3 μm, 6 μm, 12 μm, 20 μm, 45 μm and 175 μm) by the Eulerian–Lagrangian model. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 48 publications
0
55
0
Order By: Relevance
“…Our study here provides evidence for the probable airborne transmission of SARS-CoV-2 on two buses under a ventilation rate of 3.2 L/s per person or less. The importance of ventilation for SARS-CoV-2 intervention has been recently recognized in at least two major commentaries [ 30 ]; Li et al, 2021; [ [31] , [32] , [33] ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study here provides evidence for the probable airborne transmission of SARS-CoV-2 on two buses under a ventilation rate of 3.2 L/s per person or less. The importance of ventilation for SARS-CoV-2 intervention has been recently recognized in at least two major commentaries [ 30 ]; Li et al, 2021; [ [31] , [32] , [33] ].…”
Section: Discussionmentioning
confidence: 99%
“…That is why, presently, more and more works highlight the importance of achieving adequate indoor air circulations to reduce airborne transmission [ [16] , [17] , [18] ]. Although most of these works are focused on indoor environments with mechanical ventilation [ 19 ], for example, inside hospitals [ [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of indoor airflow regimes, room pressurization, and filtration for hospitals and chemical laboratories where infectious disease agents are handled were performed by Barbosa and Brum, 2018 , Liu et al, 2017 to find low-risk conditions. Ren et al (2021) studied numerical simulation of three typical ventilation strategies in a prefabricated Covid-19 inpatient ward in a hospital for a range of droplet diameters. They found that small particles move along with the main flow streams to long distances.…”
Section: Introductionmentioning
confidence: 99%